DEVELOPMENT AND VALIDATION OF A NEW RP HPLC ANALYTICAL METHOD FOR THE DETERMINATION OF ETODOLAC SUCCINIC ACID CO-CRYSTALS IN SPIKED RABBIT PLASMA - THOMAS, ANITHA; VARKEY, JOYAMMA (International Journal of Current Pharmaceutical Research, 2023)
Objective: The aim of the study was to develop and validate a novel and sensitive HPLC method for the determination of Etodolac content in Etodolac succinic acid co-crystals in spiked rabbit plasma. Methods: Chromatographic separation was achieved on an Eclipse C18 column (4.6 mm,100 mm, 3.5 μm spherical particles) using acetonitrile: methanol: acetic acid (100%) (50:49:1) as the mobile phase at a flow rate of 0.8 ml/min and monitored at 278 nm. Tinidazole was used as the internal standard. The run time was 6 min. The method was validated to fulfill International Conference on Harmonisation (ICH) guidelines, which included specificity, linearity, limit of detection (LOD), limit of quantification (LOQ), accuracy, precision and robustness. Results: The calibration curve was linear over the concentration range from 2.5 to 15 μg/ml, and the lower limit of detection was 0.3700 μg/ml. and lower limit of quantification was 1.121μg/ml for determination in spiked rabbit plasma. The accuracy and precision of the method were within the acceptable limit of±2% at the lower limit of quantification. Conclusion: A simple, sensitive, rapid and reproducible RP-HPLC method was developed with short runtime and less flow rate. Statistical analysis of the method proved that this method is suitable for the estimation of Etodolac in Co-crystalin plasma. Hence this method can be employed in the routine assay of the Etodolac Succinic acid co-crystals.